Uma Proposta de Projeto Político Pedagógico para as Escolas Estaduais Indígenas Mãtyk e Tekator: contribuições para uma Educação Escolar Apinayé Bilíngue e Intercultural. - Silva, Paulo Hernandes Gonçalves da (2024)
This thesis presents a contribution to the school education of the Apinayé people, through proposals for a Political Pedagogical Project (PPP) for the Tekator and Mãtyk State Schools, in Mariazinha and São José villages, respectively, in the municipality of Tocantinópolis/TO. The problem concerns compliance with article 78 of Law No. 9,394/1996, of the Guidelines and Bases of Education, which addresses the development of integrated teaching and research curricula for the provision of bilingual and intercultural school education to indigenous peoples. The main objective was to enunciate an open proposal for the elaboration of PPP with indications of intercultural, bilingual and transdisciplinary indigenous school education. Regarding the methodology, a bibliographic and documental review research was carried out, as well as a field investigation with an ethnographic perspective in the aforementioned villages and action research with indigenous schools - the study site. As for the theoretical contribution, the systematized knowledge established by Nimuendajú (1983), Matta (1976), Rodrigues (1986), Gadotti (1997), Pimenta (1999), Bortoni-Ricardo (2004), Albuquerque (2011), Arroyo (2012), Almeida (2015), Suanno (2015) and Zaparoli (2016). Suggestions and models for teaching mother tongue and Portuguese, as well as for traditional knowledge, were collectively constructed with the indigenous people. The results and discussions demonstrate the internal and external factors, in the coexistence between indigenous and non-indigenous, that have consequences in the school curriculum, such as mixed or interethnic marriages, contact with the majority community, evaluations of basic education and the new common national curriculum base. It was understood that the intercultural, bilingual and transdisciplinary indigenous school is consolidated in integral education, with the overcoming of the model linked exclusively to curricular components, in which all teachers, servers and those involved with the school are protagonists in the process of teaching and linguistic maintenance.